EKSISTENSI PASAR MALAM (STUDI KASUS PASAR MALAM BAYANG OHANA DI KOTA PEKANABARU) - Sihaloho, Lena Uli; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This thesis is submitted in order to qualify holds a Bachelor of Sociology. With the title "Night Market in Pekanbaru Existence". The problem addressed in this paper is to describe the shadow Ohana Night Market Profile and how to market strategy in maintaining keeksitensian night shadow night market Ohana, as well as visitors to the night market perception when viewed in terms of the game subjects were owners Night Market as well as key informant visitors night market research accindental using techniques that capture the subject at random. Researchers took the informant as many as 10 people a night market visitors, because researchers considered 10 informants visitors are able to represent other visitors. The method used is a qualitative method. Data were collected by means of observation, interviews, documents, as well as primary data and secondary data. The theory used for the existence of problems in pekanbaru night market is Max Weber's theory of social action theory that particular action instrumentasl Rationality ( zweckrationalitas ). Results of research conducted in general it can be said that the existence of the author funfair can survive because workers have a night market strategy in the face of weather disturbance problems, natural disasters or accidents games, visitors quiet, dead or damaged generators, in addition to seasonal school adaptation strategies, strategies to attract visitors also done in a way to fool visitors that are interested in games, as well as the removal or turnover strategy that is not enough. Therefore the aim of this strategy is done in order to survive the night market despite obstacles. According to the theory of gambling is a night market that contain gambling game, but from the perception, 7 more visitors bracelets like throwing game, throwing cans , rolling ball, and the game Bolling. 3 While visitors do not like and do not want to try the game, which contained the element of gambling.Keyword: Eksistensi, Socio-economic, Survival Strategies (Adaptation Strategie